Petrological implications of melanite in the rocks of the Morro de São João Alkaline Complex, Casimiro de Abreu, Rio de Janeiro, Brazil - Mariana Bessa Fagundes; Anderson Santos; Mauro Geraldes; Sérgio de Castro Valente; Eliane Guedes; Theresa Rocco Pereira Barbosa; Júlio Lopes (Brazilian Journal of Geology)
Abstract This article presents a study of the titanium-rich andradite garnet, melanite, which occurs in the rocks of the Morro de São João Alkaline Complex, of Paleocene age, located in the district of Casimiro de Abreu, southeast of the state of Rio de Janeiro, Brazil. The complex comprises felsic to mafic syenitic rocks associated with pseudoleucite. The garnet-bearing rocks are composed of a mineralogical assemblage rich in Ti and Ca, consisting mainly of alkali-feldspar, nepheline, clinopyroxene and amphiboles rich in calcium, and accessory phases containing titanite, titanite-rich magnetite, apatite, annite, and melanite. This mineral has contents of up to 4.91 wt.% TiO2, and its molecular constituents include andradite (73.54%), grossular (17.09%), and hutcheonite (9.34%). The presence of melanite, mainly associated with calcium clinopyroxene, indicates a crystallization environment characterized by conditions of high oxygen fugacity and the influence of mantle metasomatism at its source. Furthermore, as this garnet is the result of late crystallization, its presence indicates that the bearing rocks, even the most parental ones, are evolved rocks, given the low contents of MgO (< 8.14 wt.%) and Ni (< 60 ppm), as opposed to the high levels of Ba (< 10,840 ppm), Rb (< 464 ppm), and Sr (< 10,000 ppm).